Evaluation and variation trends analysis of water quality in response to water regime changes in a typical river-connected lake (Dongting Lake), China. (1st January 2021) - Geng, Mingming; Wang, Kelin; Yang, Nan; Li, Feng; Zou, Yeai; Chen, Xinsheng; Deng, Zhengmiao; Xie, Yonghong
Abstract: Lake water pollution has caused many serious ecological issues globally. An emerging public concern over water quality deterioration in lakes has heightened the need to evaluate the water quality of lakes at long-term scales, particularly for those with high hydrological alterations. This study combines the Mann–Kendall (M–K) test and self-organising map (SOM) to characterise and evaluate water quality trends in Dongting Lake, China, from 1991 to 2018, before and after the inauguration of the Three Gorges Dam (TGD). Herein, six water quality parameters were selected, namely pH, permanganate index (CODMn ), ammonia nitrogen (NH3 –N), total nitrogen (TN), total phosphorus (TP), and the five-day biochemical oxygen demand (BOD5 ). Our results show that the concentrations of TN and BOD5 increase significantly throughout the study period (|Z| ≥ 1.96). The number of abrupt change points for the six water quality parameters in the post-TGD period was greater than that in the pre-TGD period, which indicates an increased risk of water deterioration in the post-TGD period. The SOM results show that the pH values ranged from 7.64 to 7.85 among the four clusters; besides, the concentrations of the remaining water quality parameters from 1991 to 1997 and 2000 to 2003 were relatively lower, suggesting that the water quality in the pre-TGD period was better. The classification of TN and TP ranged from Level Ⅳ–Ⅴ among the clusters, which did not satisfy the level Ⅲ standard for potable water, thereby posing a higher ecological risk to the Dongting Lake. These results indicate the deterioration of the water quality in Dongting Lake during the post-TGD period under the influences of pollution load and hydrological regulation. Therefore, strict controls on the external nutrient loading and hydrological regulations should be considered for water quality management. Graphical abstract: Image 1 Abstract : The water quality deteriorated in the Dongting Lake under the influences of pollution load and hydrological regulation.